South African War books. An illustrated bibliography of English language publications relating to the Boer War of 1899-1902, R.G. Hackett : book review (Historia, 2021)
With the centenary of the outbreak of the South African War in 1999 approaching (or was it the Anglo-Boer War, the Boer War, the English War, or the Second War of Independence?) interest in this war by way of publications becomes increasingly apparent. This book, compiled by Ronald Hackett and published by P. G. de Lotz of London, is by far one of the most attractive publications yet on the South African War
Keywords: South African War; Fransjohan Pretorius; Anglo-Boer War; Ronald Hackett; Boer War Books; Ninth Division; Perthshire; military history